1999
DOI: 10.1002/(sici)1096-9896(199912)189:4<445::aid-path468>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Is dedifferentiated chondrosarcoma a ?de-differentiated? chondrosarcoma?

Abstract: Since its first description 30 years ago, dedifferentiated chondrosarcoma has been the prototype of all dedifferentiated sarcomas. The presence of two tumour portions of different mesenchymal differentiation lineages in these neoplasms gives rise to three key questions, which are on the way to being resolved. Does it split up? And if so, how does it split up and when does it split up? Accumulating data provide evidence for a common monoclonal origin of both tumour portions and suggest that dedifferentiated cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
0
9
0
2
Order By: Relevance
“…In 1998 Aigner et al [2] analysed three cases of DDCS in comparison with conventional chondrosarcoma, using different histological methods, and confirmed the prevalence of two different tumour compartments in DDCS and corroborated the hypothesis of histogenesis of two tumour portions, implying ''some sort of collision tumour'' based on the mechanism they called ''transdifferentiation'' (Aigner and Unni [1]). Molecular genetic study of one case showed a substantial number of genetic alterations, as well as severe aneuploidy and loss of heterozygosity in both components of the tumour [5].…”
Section: Discussionmentioning
confidence: 91%
“…In 1998 Aigner et al [2] analysed three cases of DDCS in comparison with conventional chondrosarcoma, using different histological methods, and confirmed the prevalence of two different tumour compartments in DDCS and corroborated the hypothesis of histogenesis of two tumour portions, implying ''some sort of collision tumour'' based on the mechanism they called ''transdifferentiation'' (Aigner and Unni [1]). Molecular genetic study of one case showed a substantial number of genetic alterations, as well as severe aneuploidy and loss of heterozygosity in both components of the tumour [5].…”
Section: Discussionmentioning
confidence: 91%
“…There is increasing evidence that tumor suppressor gene mutations play a major role in the development, progression, and /or differentiation of tumors, with p53 mutations occurring frequently in the oncogenesis of various mesenchymal neoplasms [1,2,6,7,13,20,57,60,62]. This cell line has a p53 point mutation (exon 7,codon 242 [Cys→Ser]…”
Section: Discussionmentioning
confidence: 99%
“…; p11) [9], der (11) t (8;11) [8], add (12) (p13) [3], der (12) t (12;20) (p13;?) [9], ?del (13) (q12) [8], der (13) [2], der (13;19) (q10;p10), ?idic (14) (q11) [10], der (13) (13pter→13q32::14q21→14q32::13q?) [9],-15 [3], der(15) (15qter→15p11::6p11→6p23::6?)…”
Section: Cytogenetic Examinationunclassified
“…Instead, transdifferentiation from one mesenchymal differentiated cell lineage (chondrocytic) to another (osteogenic, fibroblastic) appears to be the most likely scenario in many cases. Overall, morphological, biochemical and molecular evidence suggests two categories of dedifferentiated chondrosarcomas with a rather different cell biology [1]. One with a low grade or "benign" chondroid portion or developing secondary to a previously treated chondroid lesion as classically described by Dahlin and Beabout [21].…”
Section: Principles Of Neoplastic Chondroneogenesismentioning
confidence: 99%
“…The second subtype has a higher grade chondroid lesion and can show transition areas. Whereas in the former a late splitup of both tumor portions has to be assumed, the latter presumably shows a rather early split-up of both components [1]. However, the clinical significance of this distinction is unclear, as both subtypes appear to have a similarly poor prognosis [18].…”
Section: Principles Of Neoplastic Chondroneogenesismentioning
confidence: 99%